Knowledge of students of selected fields of study on specific eating disorders - Michał Górski; Beata Całyniuk; Jagoda Garbicz; Kamila Szynal; Karolina Górska; Renata Polaniak (Annales Academiae Medicae Silesiensis, 2023)
INTRODUCTION: Eating disorders comprise a dynamically developing group of psychiatric disorders. They are characterized by a pathological way of food intake and disturbances in the feelings of hunger and satiety. The clinical picture is dominated by destructive eating behaviours, an abnormal self-image and obsession with controlling body weight. The aim of the study was to assess the knowledge about anorexia nervosa (AN) and bulimia nervosa (BN) among students of selected faculties. MATERIAL AND METHODS: The group of respondents consisted of students of medicine, dentistry, dietetics and psychology. The questionnaire study included 955 respondents (799 women and 156 men). The probability level of 0.05 was assumed in the statistical analyses. RESULTS: More than 85% of the respondents correctly indicated the definition of AN and BN. The knowledge of the risk factors, complications, or diagnostic criteria for these conditions ranged 20–60%. The medical and psychology students had the highest level of knowledge. The respondents who had a history of eating disorders had a higher level of knowledge than those who had never suffered from them. CONCLUSIONS: The knowledge of eating disorders among medical, medical-dental, dietetics and psychology students is selective and insufficient to work with patients with eating disorders. This suggests the need for ongoing education in the researched aspect.